Capitalizing a Cure: How Finance Controls the Price and Value of Medicines - Victor Roy (University of California Press, 2023)
Capitalizing a Cure takes readers into the struggle over a medical breakthrough to investigate the power of finance over business, biomedicine, and public health. When curative treatments for hepatitis C launched in 2013, sticker shock over their prices intensified the global debate over access to new medicines. Weaving historical research with insights from political economy and science and technology studies, Victor Roy demystifies an oft-missed dynamic in this debate: the reach of financialized capitalism into how medicines are made, priced, and valued. Roy's account moves between public and private labs, Wall Street and corporate board rooms, and public health meetings and health centers to trace the ways in which curative medicines became financial assets dominated by strategies of speculation and extraction at the expense of access and care. Provocative and sobering, this book illuminates the harmful impact of allowing financial markets to determine who heals and who suffers and points to the necessary work of building more equitable futures. “An important voice on the links between finance and health ecosystems, Victor Roy makes a valuable contribution to building an economy that is based on providing health for all.” — Mariana Mazzucato, author of The Value of Everything: Making and Taking in the Global Economy and Chair of the WHO Council on the Economics of Health for All “This book is a riveting read that will strike fear in the heart of anybody who cares about the right to health or thinks that the drive for profits should not supersede democracy or human need.” — Salmaan Keshavjee, author of Blind Spot: How Neoliberalism Infiltrated Global Health “The best piece of nonfiction I have read in a long time. This book offers a fantastic, relevant, and necessary case study to understand how the financialization of the economy has affected the organization of industrial sectors.” — Marc-André Gagnon, Professor of Public Policy and Political Economy, Carleton University
Keywords: 300; Medicine; finance; biomedicine; public health